2016
DOI: 10.1016/j.bbmt.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinopathies, Bone Health, and Insulin Resistance in Patients with Fanconi Anemia after Hematopoietic Cell Transplantation

Abstract: A number of endocrinopathies have been described after hematopoietic cell transplantation (HCT), but data are limited in patients with Fanconi anemia (FA). We report several endocrine-based disorders in a cohort of 44 patients with FA after HCT compared with both 74 patients who received HCT for hematologic malignancies and with 275 healthy controls. Endocrinopathies assessed included hypothyroidism, hypogonadism, short stature, dyslipidemia, insulin resistance, abnormalities in body composition, and bone heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In fact, the present study showed that approximately half of the transplanted children and adolescent population presented Z -scores for H/age below the expected. These results are similar to the ones found by Denardi et al Barnum et al 28 performed a temporal analysis to demonstrate the association between short stature for age after HSCT and noted that under 10-year-old transplanted patients presented an incidence of short stature of 62%, while those aged between 10 and 16 presented an incidence of 50%. Patients who did not receive HSCT and were older than 16 years old did not present short stature.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, the present study showed that approximately half of the transplanted children and adolescent population presented Z -scores for H/age below the expected. These results are similar to the ones found by Denardi et al Barnum et al 28 performed a temporal analysis to demonstrate the association between short stature for age after HSCT and noted that under 10-year-old transplanted patients presented an incidence of short stature of 62%, while those aged between 10 and 16 presented an incidence of 50%. Patients who did not receive HSCT and were older than 16 years old did not present short stature.…”
Section: Discussionsupporting
confidence: 88%
“…Whether this holds true for modern fludarabine‐based regimens requires long‐term follow‐up. This may also be true for other late effects after transplant for FA, such as endocrinopathies and organ damage (Anur et al , ; Barnum et al , ). The presence of chronic GvHD is also associated with an increased risk of developing cancer (Rosenberg et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…With improved long-term survival after alloHCT, there are greater efforts to quantify and ameliorate the late effects of these endocrinopathies [117]. At the University of Minnesota [118], 44 patients with FA were followed after alloHCT with all receiving TBI 300 cGy. At least one endocrinopathy was reported in 86%, with 11% with ≥3 endocrine deficiencies.…”
Section: Introductionmentioning
confidence: 99%